2007
DOI: 10.1210/jc.2007-0219
|View full text |Cite
|
Sign up to set email alerts
|

Surgery or Surveillance for Mild Asymptomatic Primary Hyperparathyroidism: A Prospective, Randomized Clinical Trial

Abstract: Context:It is unclear whether patients with asymptomatic primary hyperparathyroidism (PHPT) do better with parathyroidectomy (PTx) as compared with conservative medical management. Objective:The aim of the study was to evaluate the beneficial effect of PTx vs. conservative management in patients with mild asymptomatic PHPT. Design:We conducted a prospective, randomized study. Setting:The study took place at a referral center. Patients:We studied 50 patients who did not meet any guidelines for parathyroid surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
300
0
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 354 publications
(327 citation statements)
references
References 30 publications
12
300
0
15
Order By: Relevance
“…Three randomized clinical studies were conducted to evaluate the effect of PTx versus conservative treatment in patients with mild PHPT on neurocognitive symptoms, among other manifestations (57,68,69) (see details in the "Effects of Parathyroidectomy" section). The data from these studies suggest a significant difference in favor of surgical treatment (A-1A).…”
Section: Neuropsychiatric Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three randomized clinical studies were conducted to evaluate the effect of PTx versus conservative treatment in patients with mild PHPT on neurocognitive symptoms, among other manifestations (57,68,69) (see details in the "Effects of Parathyroidectomy" section). The data from these studies suggest a significant difference in favor of surgical treatment (A-1A).…”
Section: Neuropsychiatric Manifestationsmentioning
confidence: 99%
“…Randomized studies (57,68,69), but with limited follow-up time (1-3 years) have demonstrated benefits in quality of life and BMD in asymptomatic patients who undergo surgery (A-1B).…”
Section: Diagnosis and Management Of Primary Hyperparathyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…At pasienter enkelte steder i Norge blir henvist til og tilbudt behandling for primaer hyperparatyreoidisme og andre steder ikke, skyldes nok at det mangler godt dokumenterte kriterier for kirurgi ved tilstanden, spesielt ved såkalt asymptomatisk hyperparatyreoidisme (3,4).…”
Section: Er Det Behov For Nasjonale Retningslinjer?unclassified
“…I tillegg rapporterer mange pasienter symptomer som blant annet nedstemthet, at man lett blir trett, søvnpro-blemer og konsentrasjonsvansker (2). At kirurgisk behandling har effekt på de klassiske symptomene er veldokumentert, men fordelene med kirurgi hos pasienter uten de klassiske symptomene er omdiskutert (3,4). Retningslinjer for operasjonsindikasjoner ble vedtatt av en tverrfaglig internasjonal ekspertgruppe på en konsensuskonferanse ved National Institutes of Health i 1990 og revidert i 2002 (ramme 1) (5).…”
unclassified